2022
DOI: 10.3389/fpsyg.2022.944238
|View full text |Cite
|
Sign up to set email alerts
|

Developmental assets, creativity, thriving, and mental health among Malaysian emerging adults

Abstract: This study was part of a larger cross-national research project at the Norway’s University of Bergen, which involved participants from over 30 countries. This undertaking delves into developmental assets, creativity, and thriving, and the part they play in determining mental health. Thus, this study examined the developmental assets (internal assets: support, empowerment, boundaries, and expectations and creative use of time; external assets: commitment to learning, positive identity, positive values, and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…AGMZH's acknowledgment of prevailing prejudices and the call for embracing cultural competence underscore the crucial role of youth in challenging and mitigating societal biases and in fostering a more inclusive and tolerant society [21]. These insights also support the evident importance of various developmental assets in supporting the development of young individuals experiencing mental health challenges [14,31,32].…”
Section: Discussionmentioning
confidence: 91%
“…AGMZH's acknowledgment of prevailing prejudices and the call for embracing cultural competence underscore the crucial role of youth in challenging and mitigating societal biases and in fostering a more inclusive and tolerant society [21]. These insights also support the evident importance of various developmental assets in supporting the development of young individuals experiencing mental health challenges [14,31,32].…”
Section: Discussionmentioning
confidence: 91%
“…It is also worth highlighting the predominance of studies with a cross-sectional observational design and, to a lesser extent, studies with a longitudinal, prospective design. [39] 2) Malaysia Results revealed that all the variables were positively correlated to each other; the relationship between development assets, creativity, thriving, and mental health ranged from weak to moderate. Multiple regression (stepwise) analysis produced four models that indicated that positive identity, support, creativity, and thriving have a significant influence on mental health among emerging adults.…”
Section: Resultsmentioning
confidence: 97%
“…While internal and external assets are individually important for young people's lives, their interaction is considered vital for fostering strength, character, and receiving guidance and opportunities from family, school, and society (Abdul Kadir & Rusyda, 2022;Gan et al, 2022). Drawing from the Positive Youth Development Approach, this study focuses on positive growth concepts that facilitate youth flourishing, achievement, and intelligent interactions with others and life events.…”
mentioning
confidence: 99%
“…Moreover, they are more likely to exhibit caring behaviors toward their family, others, and the community, as a response to the positive environment they have experienced. In other words, youth perceive a high sense of connection between themselves and the adults in their context, which fosters their productivity and involvement in society (Abdul Kadir & Rusyda, 2022;Dost-Gözkan et al, 2021;Sui et al, 2021). Lastly, youth who possess social skills or who are situated within a supportive school environment are more likely to develop a commitment to learning and social competencies (Wiium et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation